Diabetic ketoacidosis as first presentation of undiagnosed pancreatic cancer in an octogenarian - Minh V Le; Spiros Fourlanos; Rahul D Barmanray (Endocrinology, Diabetes & Metabolism Case Reports)
Diabetic ketoacidosis (DKA) is a complication of diabetes melli tus (DM) that can theoretically occur in people of any age. While DKA can typically be the first pr esentation of type 1 DM in younger people, a first pr esentation is rare in older adults. Pancreatic cancer often manifests with new DM or hyperglycaemia, but very rarely as DKA. We report a case of an 89-year-old woman who was incidentally diagn osed with DKA during workup for an unwitnessed fall. Her DKA was promptly managed, and she was subsequently diagnosed with metasta tic pancreatic cancer. Given the advanced stage of her malignancy, the multidisciplinary team consensus was for a palliative approach. She passed away on day 10 of the admission. T o our knowledge, this is the first report of a first DKA presentation as a manifestation of pancreatic cancer in an adult aged over 70 years. To date, there is no effective screening test for pancreatic cancer in the general population. However, new-onset DM in the appropriate context might indicate the need for further evaluation. While it is possible that unresectable tumours are identified, earlier diagnosis of DM with pancreatic cancer may facilitate more timely management, including earlier advanced care planning.